Development of An Indonesian Language Teaching Module Based on The iSpring Suite Application for Elementary School Students - Dina Erina Nasution; Marlina Marlina (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This research aims to develop an Indonesian language teaching module based on the iSpring suite application for class II elementary school students. This research method used research and development (R&D) with the ADDIE model, which includes stages: Analysis, Development, Design, Implementation, and Evaluation. Three elementary schools in West Sumatra conducted this research. Data collection used observation sheets, questionnaires, interviews, validation instruments, practicality questionnaires, and evaluation tests. This research data analysis technique collected all the necessary data, namely from the results of module validation, module practicality and module effectiveness, and the N-Gain test. The teaching module validity test results obtained an average score of 4.34 in the very Good category. The results of the practicality test of the teaching module, teacher, and student responses obtained an average score of 4.45 in the very practical category. The effectiveness test can be seen from the results of the student knowledge test before the pretest and posttest question difficulty level. The test results at three elementary schools showed that the modules and tests could be declared effective; the average N-Gain Score was 58.23 in the quite effective category. The teaching module has proven to be very good, practical, and quite effective.